Extradural hematoma in Baghdad Neurology surgery hospital - zamil, kadhim H. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Extradural hematoma (epidural hematoma) result from tearing of dural or skull vessels caused by deformation of the skull or fracture. Epidural hematoma can occur at all ages but are seen primarily in patients younger than 60 years. Patients and Methods: this prospective study was conducted on 50 patients (38 male, 12 female) suffering from head injury and has a CT scan evidence of extradural hematoma during the period from 1 January 2006 to 31 December 2008 in Neurology surgery hospital. Results: There were 4 patients above 50years, the cause of injury was fall in50%, assault24%, RTA20%and bullet injury 6%.the commonest site was temporal region 42%.surgical treatment were done to 39 patients, Middle meningeal artery and its branches was the source of bleeding in 42%, full recovery achieved in 62%, post operatively 4patients suffered from anaemia, one of them required blood transfusion. Conclusion: Extradural hematomas are life-threatening injury should be treated by surgery and conservative treatment only for small EDH with no symptoms and remain so or disappear by Serial follow-up CT scan